Innovate or litigate? The dual impacts of multimarket contacts on global competition - Giachetti, Claudio; Onoz, Ergun; Yu, Tieying (Journal of International Business Studies, 2026)
Abstract Our study, grounded in the multimarket competition, knowledge management, and technological change literature, investigates how multimarket contacts among multinational enterprises—i.e., the extent to which rival multinational enterprises meet simultaneously in multiple countries—shape their innovation and patent litigation decisions in host countries. We propose that the degree of multimarket contacts a multinational enterprise has with its competitors in a host country may restrain it from aggressively launching product and technological innovations in that country due to a fear of cross-country retaliation. However, increased multimarket contacts also facilitate knowledge diffusion, heightening the risk of imitation, and consequently enhance the multinational enterprise’s patent litigation intensity—a means to protect knowledge-based resources—in that country. Moreover, we examine how two features of the host-country technological environment—technological ferment (an era of intense technical variation following a technological discontinuity until a dominant design emerges) and home–host country differences in intellectual property protection—moderate these relationships. We test our hypotheses using a dataset of 85 mobile phone vendors, which includes data on their products and technological innovations and litigation cases in 46 countries between 2003 and 2015. This study sheds light on the interplay among multinational enterprises’ multimarket contacts, innovation, and patent litigation.